Metabolites Profiling of Melanoma Interstitial Fluids Reveals Uridine Diphosphate as Potent Immune Modulator Capable of Limiting Tumor Growth - Vecchio, Eleonora; Caiazza, Carmen; Mimmi, Selena; Avagliano, Angelica; Iaccino, Enrico; Brusco, Teresa; Nisticò, Nancy; Maisano, Domenico; Aloisio, Annamaria; Quinto, Ileana; Renna, Maurizio; Divisato, Giuseppina; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tumor interstitial fluid (TIF) surrounds and perfuses tumor and collects ions, metabolites, proteins and extracellular vesicles secreted by tumor and stromal cells. Specific metabolites, accumulated within TIF, could induce metabolic alterations of immune cells and shape tumor microenvironment. We deployed a metabolomic approach to analyze the composition of melanoma tumor interstitial fluid and compare it to plasma of C57BL6 mice, engrafted or not with B16-melanoma cells. Among the classes of metabolites analyzed, mono- and diphosphate nucleotides resulted enriched in TIF compared to plasma samples. The analysis of the effects exerted by GDP and UDP on immune response revealed that GDP and UDP increased the percentage of CD4+CD25+Foxp3- and, on isolated CD4+ T-cells, induced the phosphorylation of ERK, STAT1, STAT3, increased the activity of NF-kB subunits p65, p50, RelB and p52 as well as increased the expression of Th1/Th17 markers including IFNgamma, IL17, T-bet and RORgammat while reduced the expression of IL13, a Th2 marker. Finally, we observed that local administrations of UDP in B16-engrafted C57BL6 mice reduced tumor growth and necrotic areas. In addition, UDP-treated tumors showed a higher presence of MHCIIhi TAM and of CD3+CD8+ and CD3+ CD4+ TILs, both makers of anti-tumor immune response. Consistent with this, intra-tumoral gene expression analysis revealed in UDP-treated tumors an increase in the expression of genes functionally linked to anti-tumor immune response. Our analysis revealed an important metabolite acting as mediator of immune response, which could potentially represent an additional tool to be used as an adjuvant in cancer immunotherapy.